CONTENT ANALYSIS OF THE LEXICAL DENSITY OF THE ENGLISH FOR ISLAMIC STUDIES TEXTBOOK OF IAIN RADEN INTAN LAMPUNG - Hidayat, Agus (English Education: Jurnal Tadris Bahasa Inggris, 2015)
The objective of this study is to analyze the lexical density of the texts of English for Islamic Studies of IAIN Raden Intan Lampung. The writer conducted this study to find out the lexical density of the texts included in the textbook that is commonly used as an instructional material for the students of non-English Education Study Program in their English Subject. The type of the study used in this case is descriptive qualitative research. This study is done by analyzing fourteen (14) texts presented in the textbook by determining the content words and grammatical words and then calculating the amount of the content words divided to the total words of each text. Based on the analysis, it was found that seven texts contained in the textbook of English for Islamic studies are in the low lexical density category, six  texts are in the normal category, and one  text is in the high lexical density categories.